2012
DOI: 10.1021/ic301050v
|View full text |Cite
|
Sign up to set email alerts
|

Positive Surface Charge Enhances Selective Cellular Uptake and Anticancer Efficacy of Selenium Nanoparticles

Abstract: Surface charge plays a key role in cellular uptake and biological actions of nanomaterials. Selenium nanoparticles (SeNPs) are novel Se species with potent anticancer activity and low toxicity. This study constructed positively charged SeNPs by chitosan surface decoration to achieve selective cellular uptake and enhanced anticancer efficacy. The results of structure characterization revealed that hydroxyl groups in chitosan reacted with SeO(3)(2-) ion to form special chain-shaped intermediates, which could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(156 citation statements)
references
References 41 publications
10
145
1
Order By: Relevance
“…The resultant nanoparticles had a positive zeta potential (19.8 mV), which could be attributed to the octadecylamine with an added ammonium group [35] . It has been demonstrated that nanoparticles with a positive charge are [36] . Additionally, the Malvern Nano-ZS90 laser particle size results showed that the Bre-NLC had a narrow particle dispersion of ~170 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant nanoparticles had a positive zeta potential (19.8 mV), which could be attributed to the octadecylamine with an added ammonium group [35] . It has been demonstrated that nanoparticles with a positive charge are [36] . Additionally, the Malvern Nano-ZS90 laser particle size results showed that the Bre-NLC had a narrow particle dispersion of ~170 nm.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 However, there are very few reports on the anticancer activity of SeNPs synthesized by bacteria. 37,48 SeNPs synthesized by Bacillus strain ZYK have profound anticancer activity against H157 lung cancer cell line.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…38 Earlier, we demonstrated that the zeta potential of MLP increased significantly under hypoxic and low-pH conditions. Whether MLP could enhance the cellular uptake under hypoxic and low-pH conditions, and the cellular uptake and intracellular distribution of the MLP/siRNA were studied by fluorescence microscopy and flow cytometry.…”
Section: Intracellular Uptake Of Mlp/sirna By C6 Cellsmentioning
confidence: 86%